Exploring the Islamic approach to Halal science: analysis of Ijtihad methodology for determining permissibility and prohibition of blood plasma in food additives - Busari, Saheed Abdullahi (HH Publisher, 2024)
The significance of the Islamic principles of Halal and haram to a sustainable society cannot be overemphasized in the current global struggle against socio-economic, medical, and environmental issues. Halal science products and services are becoming attractive to corporate industries, especially in the food industry. Although related studies in the Halal industry have been gaining attention in recent times, with the global economic outlook to hit $4.96 trillion by 2030, little is known about the research that speaks to the fundamental Islamic principles of halal and haram in the food and services industries. Modern industries are conscious of employing workers who can contribute to the sustainability of the business amid the emerging contemporary realities. This study explicates contemporary Ijtihad methodology of Taḥqīq manāt al-hukm (verifying causal effect existence) and takhrīj manāt al-hukm (coming up with effective cause) in food additives like blood plasma content. To this effect, the study employs qualitative methodology in data gathering and analysis of classical and contemporary literature reviews. This study found that comprehensive Ijtihad methodology and application is a necessity for understanding the modern realities of Halal and Haram in food additives using blood plasma contents.